The incidence of intrathoracic tumours in Manchester, 1868-1926 - Greenberg, Morris; Trott, Peter A. (European Journal of Oncology and Environmental Health, 2017)
Dr J. B. Duguid published a paper in 1927 entitled "The incidence of intrathoracic tumours in Manchester”. It was based on autopsies conducted at the Manchester Royal Infirmary between 1868 and 1926. While the majority of intrathoracic tumours had been diagnosed as bronchogenic carcinomas, there remained a small number affecting the pleura about which there had been uncertainty. Lancashire had been the cradle of Britain’s asbestos industry: Turner Brothers Asbestos had converted a cotton mill to asbestos in Rochdale in 1880, and had built another factory in Manchester in 1913, so that there would have been time enough for the development of asbestos associated malignancies. When in 1991 hindsight prompted a review of the Manchester clinical and autopsy materials, it was discovered that they had all been disposed of recently. The published descriptions of histopathological appearances in the uncertain cases were reviewed and it was concluded that, while it was impossible categorically to identify these lesions as mesothelial in phenotype, the anatomical site and the description offered the possibility. It is a matter of conjecture whether the identification of malignant mesothelioma in association with exposure to asbestos in 1926, would have prompted effective action to avert a major international public health disaster.